2019
DOI: 10.1029/2018wr023265
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Fluxes and Age Distribution of Soil Water, Plant Water, and Deep Percolation in a Model Tropical Ecosystem

Abstract: Recent field observations indicate that in many forest ecosystems, plants use water that may be isotopically distinct from soil water that ultimately contributes to streamflow. Such an assertion has been met with varied reactions. Of the outstanding questions, we examine whether ecohydrological separation of water between trees and streams results from a separation in time, or in space. Here we present results from a 9‐month drought and rewetting experiment at the 26,700‐m3 mesocosm, Biosphere 2‐Tropical Rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 94 publications
9
95
4
Order By: Relevance
“…It has to be noted that our findings might be slightly biased towards soil water uptake as groundwater data were not considered in our study. However, our findings are in line with previous studies and meta‐analyses showing that trees across most climate zones predominantly rely on soil water (Bowling, Schulze, & Hall, ; Brooks, Barnard, Coulombe, & McDonnell, ; Evaristo et al, ; Geris, Tetzlaff, McDonnell, & Soulsby, ; Grossiord et al, ; Gu et al, ; Rose, Graham, & Parker, ; Rossatto, de Carvalho Ramos Silva, Villalobos‐Vega, Sternberg, & Franco, ; Wei, Fang, Liu, Zhao, & Li, ; Yang & Fu, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has to be noted that our findings might be slightly biased towards soil water uptake as groundwater data were not considered in our study. However, our findings are in line with previous studies and meta‐analyses showing that trees across most climate zones predominantly rely on soil water (Bowling, Schulze, & Hall, ; Brooks, Barnard, Coulombe, & McDonnell, ; Evaristo et al, ; Geris, Tetzlaff, McDonnell, & Soulsby, ; Grossiord et al, ; Gu et al, ; Rose, Graham, & Parker, ; Rossatto, de Carvalho Ramos Silva, Villalobos‐Vega, Sternberg, & Franco, ; Wei, Fang, Liu, Zhao, & Li, ; Yang & Fu, ).…”
Section: Discussionsupporting
confidence: 92%
“…Plants can access shallow and deep soil water, as well as groundwater with a tendency to prioritize the use of stable and continuous water sources (Zhao & Wang, ), at least in regions where some sources are continuously available. Several studies based on an isotope approach and focusing on the identification of different water sources accessed by plants have been conducted at individual sites in many regions of the world and on different plant species (e.g., to name a few recent studies, Allen, Kirchner, Braun, Siegwolf, & Goldsmith, ; Chi, Zhou, Yang, Li, & Zheng, ; Dubbert, Caldeira, Dubbert, & Werner, ; Evaristo et al, ; Nie et al, ; Oerter, Siebert, Bowling, & Bowen, ; Qiu et al, ). Recent meta‐analyses assessed plant water sources across different biomes and plant species (Barbeta & Peñuelas, ; Evaristo, Jasechko, & McDonnell, ; Evaristo & McDonnell, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Flow‐generating subsurface water fluxes mostly originate from water in the larger, drainable (macro)pores, which can bypass the matrix with little exchange or mixing (Figure b). Such preferential flow was observed in lysimeter studies where younger water that bypassed older water were observed in the outflow via stable isotope measurements (Benettin et al, ; Evaristo et al, ; Stumpp & Maloszewski, ). The age of the percolating water can also vary with the redistribution of soil water into the soil matrix due to macropore‐matrix interactions (Klaus et al, ) and due to soil heterogeneity (Danesh‐Yazdi et al, ).…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 74%
“…2 H and 18 O can also be used to identify paleo‐groundwater, because the isotopic composition of precipitation (and thus groundwater recharge) was different during the Pleistocene (ending 11,700 years ago) under a different climate (e.g., Rozanski, ; van Geldern et al, ). The timescale of artificially introduced tracers like Br ‐ , SF 6 , dyes (e.g., brilliant blue), or isotopically enriched water (“deuterated” enriched in 2 H; enrichment in 18 O is also possible) during sprinkling or injection experiments mainly depends on the tracer breakthrough curve in the monitored flux and the observation limits in the studied compartment (e.g., groundwater in Becker & Coplen, ; soil and lysimeter outflow in Koeniger et al, ; Evaristo et al, ; transpiration in Bachmann et al, ; Beyer et al, ; Volkmann, Haberer, et al, ).…”
Section: Quantifying Water Ages In the Critical Zonementioning
confidence: 99%
“…Alternatively, temporal variation of snowmelt versus irrigation fractions might not reflect a switch toward deeper water sources with greater snowmelt contribution but instead might be explained by variability in stem water transit times, which may vary by several months depending on the species physiology and stem water storage capacity(Evaristo et al, 2019). Thus, it is possible that irrigation does not fully replenish soil moisture by the end of the growing season after summer-long evaporative and transpiration losses, such that residual snowmelt in deeper soil layers becomes a more important additional source of plant transpiration.…”
mentioning
confidence: 99%